Response to: Correspondence on “Complications of HIPEC for ovarian cancer surgery: evaluation over two time periods” by Lavoue et al - Navarro Santana, Beatriz; Viveros-Carreño, David; Ramirez, Pedro T (International journal of gynecological cancer, 2024)
Ostomy is associated with poor quality of life and it has its own associated complications which were not reported in the article. [...]in the study by Lim et al,4 the HIPEC group had higher prothrombin time and more nephrotoxicity than the surgery alone group. [...]the HIPEC group had a longer operative time (506.5 min vs 384 min) and longer hospitalization (median of 17 vs 14 days). [...]looking at these data, we cannot affirm that interval surgery with or without HIPEC is truly associated with similar complication rates. [...]in the 2024 ESGO-ESMO-ESP consensus conference recommendations on ovarian cancer8 there was no agreement reached as it pertains to routine use of HIPEC in the interval setting.